Improving students’ reading comprehension on procedure text by using demonstration method at grade IX A SMPN 1 Kerinci in first semester of 2017/2018 academic year - Irzal Wadi; Mukhaiyar Mukhaiyar; Hamzah Hamzah (Fakultas Ilmu Pendidikan UNP)
This research is designed to improve the students’ reading comprehension on procedure text by using demonstration method. This is aimed at finding whether demonstration method can improve students’ reading comprehension on procedure text at Grade IX A SMPN 1 Kerinci in First Semester of 2017/2018 Academic Year. The study employed a classroom action research design in which the researcher and his collaborator worked together in designing the lesson plan, implementing the action, analyzing the data, and doing the reflection. The participants of this research were 23 students at Grade IX A SMPN 1 Kerinci in First Semester of 2017/2018 Academic Year. The research finding was that demonstration method could improve the students’ reading comprehension. This conclusion was based on the increasing of the average score of students’ reading comprehension. The students’ average score before conducting the method was only 57,39, then it increased to 73,04 in cycle one. And it became 77,82 in cycle two. It means that students’ average score successively improved in each cycle. And it can achieve the minimum achievement criteria or KKM, 70. Furthermore, factors that influence teaching and learning process are material, media, classroom activity, classroom management, teacher’s approach, and teaching strategy.